Multisensory Causal Inference in the Brain - Kayser, Christoph; Shams, Ladan (PLOS Biology, 2015)
How does our brain organize and merge multisensory information? A new study localizes the brain regions underlying sensory fusion and causal inference by combining neuroimaging and computational modelling.